Implementasi Transaksi Non Tunai Terhadap Penerimaan Pajak Daerah dan Retribusi Daerah Pada Badan Pendapatan Daerah Kabupaten Sidenreng Rappang - Elsye Febryani Paramean; Amir Jaya; Corvis Rantererung (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
This research aims to describe and analyze the implementation of non-cash transactions, supporting and inhibiting factors as well as solutions taken in the process of implementing non-cash transactions on regional tax revenues and retributions at Badan Pendapatan Daerah Kab. Sidenreng Rappang. This research is research that uses a descriptive qualitative approach. Data collection techniques through interviews, observation and documentation are validated using source triangulation and technical triangulation and then analyzed through data condensation, data presentation and drawing conclusions/verification. The research results show that the implementation of non-cash transactions has increased from 49.15% in 2022 to 86.89% in 2023 of total revenues each year. The supporting factors are regulations and support from the Central Government, South Sulawesi Provincial Government, Bank Indonesia and Bank Sulselbar. The challenges faced include several remote areas where the internet network has not been reached and there are still a group of people whose literacy level is still low, so the solution that can be taken is to coordinate with related agencies to expand the reach of the internet network and increase socialization for people in areas where cash transactions are high.